Adaptation of the Mertz-Hong Reactance Scale in a Russian-speaking Sample - N.V. Nichko; S.D. Gurieva (Социальная психология и общество)
Objective. The article presents the results of adaptation of the Mertz–Hong reactance scale on a Russian-speaking sample. Background. The world will no longer be the same, and we will not remain as we were before. The pandemic and the consequences of the economic crisis have provided a powerful impetus for changes in Russian society, organization functioning, and people's habitual way of life. The theory of reactive resistance helps to explain these changes and reactions, seeing them as a response to the threat to personal freedom from external influences. The study of the theory contributes to the development of effective strategies for communicating and managing behavior in new realities. The use of an adapted version of the Mertz–Hong Reactive Resistance Scale will help fill the deficit of Russian-language psychometric instruments designed for the theoretical and empirical study of reactive behavior, helping to better understand the processes of psychological influence and resistance. Study Design. The study was conducted using the Online Test Pad service in 2024. Participants. The pilot sample included 32 respondents, the final sample included 218 respondents: 61 men (28%), 157 women (72%) from different regions of the Russian Federation. Age from 18 to 75 years, M = 35,2; SD = 13,3; more than half (66,5%) have higher education. Measurements. The reactive resistance model of S.-M. Hong was used as the basis of the scale. The correlations with socio-demographic indicators, internal consistency, and test-retest reliability were checked. Factor validity was verified by the method of principal components with varimax rotation and confirmatory factor analysis. SPSS 26.0 and Jamovi 2.6.2 were used for data processing. Results. A four-factor scale structure was obtained, Cronbach's alpha = 0,812; McDonald's ω = 0,823; Retest reliability after 4-5 weeks (48 people), Pearson's r = 0,746 (p = 0,01). Using confirmatory factor analysis, a model with the following indicators was obtained: CFI 0,931; TLI 0,906; SRMR 0,053; RMSEA 0,059; lower 0,040 upper 0,078. Conclusions. Despite the multiple criticisms of the original Merz and Hong’s scales, we have obtained a good intermediate model that can be used as a tool, however, further refinement and verification of a number of indicators are necessary.